Patterns of Vegetation and Climatic Conditions Derived from Satellite Images Relevant for Sub-Antarctic Rangeland Management - Villa, Madeleyne; Opazo, Sergio; Moraga, Claudio A.; Muñoz Arriagada, Rene Santiago; Radic Schilling, Sergio Javier (My University, 2020)
Sub-Antarctic rangelands are characterized by weather seasonality and abundant winter snowfall. These climate factors determine most livestock management decisions. Nonetheless, data on these weather patterns are only available for some areas of the region, and management is entirely empirically-derived. The aim of this study was twofold: to compile spatial and temporal environmental information of rangelands in the Magallanes Region of Chile by using satellite images and to provide an example for local purposes through a simple evaluation of current grazing systems of four ranches in central Tierra del Fuego using satellite-derived image products and a known thermal comfort zone for sheep. To determine the environmental conditions of the region, we processed a 12-year (2000-2011) series of three MODIS-Terra platform products: Normalized Difference Vegetation Index (NDVI) as an index of photosynthetic activity, snow cover index, and Land Surface Temperature (LST). Results indicate that data obtained from satellite images follow the known seasonality of the region and deliver spatial and temporal environmental information (e.g., temperature at large scale) for most ranching areas of the region where it was formerly unavailable. The determined grazing period of analyzed ranches for winter range was May 8 to September 29. These tools show promise to encourage management innovation from simple applications to combine platforms and models for forage monitoring and ranch management in Sub-Antarctic rangelands. (C) 2020 The Society for Range Management. Published by Elsevier Inc. All rights reserved.
Keywords: snow cover; lst; modis; ndvi; sheep ranching; extensive production